Standard Test Method for Through-Thickness "Flatwise" Tensile Strength and Elastic Modulus of a Fiber-Reinforced Polymer Matrix Composite Material1 - Astm
This test method determines the through-thickness "flatwise" tension strength and elastic modulus of fiber reinforced polymer matrix composite materials. A tensile force is appliednormal to the plane of the composite laminate using adhesively bonded thick metal end-tabs. The composite material forms are limited to continuous-fiber or discontinuous fiber (tape or 2-dimensional fabric, or both)reinforced composites
Keywords: POLYMER MATRIX COMPOSITE